Pengaruh Reward Dan Punishment Terhadap Kinerja Karyawan Pada PT Hydrocore Kota Tangerang Selatan - Heni Purwasih; Esti Suntari (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research aims to determine the effect of reward and punishment on employee performance at PT Hydrocore South Tangerang City, both partially and simultaneously. The method used is quantitative methods. The research sample was 80 respondents. Data analysis methods used in research include instrument tests consisting of validity tests, reliability tests, classical assumption tests consisting of normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression tests, correlation coefficients, coefficient of determination tests, hypothesis tests consisting of partial t test and simultaneous f test. The research results show that rewards have an influence on employee performance with a value of t_count > t_table or (11.822 > 1.991) and a significance value of 0.000 < 0.05. Thus, 〖Ho〗_1 is rejected and H_1 is accepted. Punishment has a positive and significant influence on employee performance with a t_count > t_table or (11.666 > 1.991) and a significance value of 0.000 < 0.05. Thus, 〖Ho〗_2 is rejected and H_2 is accepted. Reward and punishment have a positive and significant influence on employee performance with a value of F_count > F_table or (84.654 > 3.120) and a significance value of 0.000 < 0.05. Thus, 〖Ho〗_3 is rejected and H_3 is accepted. Reward and punishment on employee performance have an influence. The R-square value (coefficient of determination) is 0.687, so it can be concluded that the reward (X1) and punishment (X2) variables together have an influence contribution to the employee performance variable (Y) of 68 .7%, while the remaining 31.3% is influenced by other factors or variables that were not studied.